2012
DOI: 10.4161/gmcr.21365
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cormlet production of saffron (Crocus sativus L. Kashmirianus) and their flowering response under greenhouse

Abstract: A complete protocol for the saffron cormlet production under in vitro conditions and subsequent flowering under greenhouse conditions is described. Highest number of cormlets (70.0 ± 0.30) per corm slice (explant) could be regenerated on Murashige and Skoog (MS) half strength medium supplemented with thidiazuron (TDZ) (20 µM), Indole acetic acid (IAA) (10 µM), and sucrose (40 g/l). Maximum germination (90%) of these cormlets could be achieved on MS medium containing 6-benzyl amino purine (BAP) (20 µM) and α-na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
1
14
0
2
Order By: Relevance
“…• C under 16-h photoperiod, illuminated with cool white fluorescent tubes (7400 lux) (Parray et al 2012). The best media combination MS (1/2) + BAP(20 µM ) + NAA(20µM ) + sucrose(30 g l −1 ) was identified based on the callus formation efficiency (Figure 1).…”
Section: Callus Formationmentioning
confidence: 99%
“…• C under 16-h photoperiod, illuminated with cool white fluorescent tubes (7400 lux) (Parray et al 2012). The best media combination MS (1/2) + BAP(20 µM ) + NAA(20µM ) + sucrose(30 g l −1 ) was identified based on the callus formation efficiency (Figure 1).…”
Section: Callus Formationmentioning
confidence: 99%
“…During the last two decades or so, number of media have been used by various researchers for in vitro studies in Saffron. Comparative studies have been undertaken between Murashige and Skoog (MS) and Linsmaier and Skoog (LS) media [18], LS for callogenesis and organogenesis [19], B5 for indirect and direct regeneration [20] and 1/2MS for direct regeneration of shoot in saffron [21]. In the present studies we used complete MS medium as it has been shown to be the best suited medium for complete propagation of saffron.…”
Section: Callus Production From Corm Slices In Vitro and Regenerationmentioning
confidence: 99%
“…Among the cytokinins used in earlier studies, TDZ was independently capable to induce shoot regeneration whereas BAP, zeatin and Kn required auxins to stimulate multiple shoots [20]. Parray et al demonstrated very high efficiency of TDZ in regenerating over 70 cormlets per slice of corm when they used 1/2MS supplemented with TDZ and IAA [21]. In our study, significant increase in biomass and mean number of somatic embryos was observed after using TDZ with IAA in the medium (Table 2).…”
Section: Cytokinins Auxins and Carbohydrate Source For Cormlet Produmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants are vital curative agents for curing human ailments. The overexploitation of natural plant resources encouraged various programs such as conservation, micropropagation, and incremental plant architecture [ 1 , 2 ]. Looking at the present scenario, a significant proportion of the Northwest Himalayan (NWH) medicinal herbs, particularly Arnebia benthamii (Wall.…”
Section: Introductionmentioning
confidence: 99%